Sekolah Pasar Rakyat Sambilegi, Alternatif Pendidikan Agama Islam Dalam Masyarakat - Khilda Maulidiah; Siti Aisyah; Muhammad Nasrudin (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2017)
This paper intends to see one form of public education in Indonesia in the perspective of Islamic Education. The object of this research is the Sambilegi tradisonal Market School (SPRS) located in Sleman Regency. From the data obtained through observation, interviews and observations it can be concluded that the principle of togetherness in welfare which is the basis of organization and education is an important value for its conformity with the principles of Islamic education. Supporting and inhibiting factors in SPRS education are indeed found, but togetherness commitments need to be deepened as long as education is even disseminated.